ANALYZING LEGAL DIMENSIONS OF PRODUCT SCANDAL IN INDONESIAN INSURANCE DISTRIBUTIONS: MIS-SELLING UNIT-LINKED CASE - Putri J, Pramai Shella Arinda; Anadi, Yandri Radhi (Kanun Jurnal Ilmu Hukum, 2024)
Insufficient consideration of inflation in pricing can result in insurance premiums being set too low, threatening the long-term viability of the insurance industry. This challenge became particularly evident during the notable challenges experienced by the Indonesian insurance industry between 2021 and 2022. Various issues, including poor management, product mis-selling, and the sale of unit-linked products with inaccurate information, led to insurance customers protesting against the Financial Services Authority (OJK) and the bancassurance sector, which is a partnership between banks and insurance companies that allows banks to sell insurance products through their distribution networks. This study analyzes the legal dimensions of insurance agent misconduct in mis-selling insurance products and propose targeted strategies for regulatory and industry reforms led by OJK to foster a healthier and more transparent Indonesian insurance sector. This study employed a normative legal research method with a statute- and concept-based approach. The results show improper sales violate Article 75 of Indonesias Insurance Law (Law No. 40 of 2014). The cumulative effect of these violations can damage the insurance sector's reputation, leading consumers to view it as unreliable and predatory, which may reduce market participation as potential policyholders opt-out, ultimately undermining the financial stability and growth of the insurance market in Indonesia. In response, the OJK has introduced SEOJK No. 5/SEOJK.05/2022, which provides guidelines for implementing risk-based supervision in the insurance sector. This regulation enhance transparency and accountability, address the identified issues, and restore consumer trust in the Indonesian insurance market.